1998
DOI: 10.1080/009841098159367
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Cholestyramine Reduces Ochratoxin a-Induced Nephrotoxicity in the Rat by Decreasing Plasma Levels and Enhancing Fecal Excretion of the Toxin

Abstract: Ochratoxin A (OTA) is a mycotoxin that may contaminate animal feed (oat, barley, and rye) and food (wheat, rice, coffee, beer, pig meat), leading to major health problems (e.g., nephropathy) in several animal species including humans. Several methods have been tested to reduce the toxicity of OTA in animals but with limited success. In rats, the effect of cholestyramine (CHA), a bile acid-binding resin, was investigated on OTA-induced nephrotoxicity and bioavailability. Animals were fed semisynthetic diets con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Animal studies involving the use of CSM for OTA exposure have shown it accomplishes the therapeutic goal of reducing plasma levels of OTA while enhancing fecal excretion of the toxin bound to CSM. A study was able to demonstrate decreased nephrotoxicity in rats exposed to OTA that were given CSM, by reducing plasma and urine values of OTA while increasing fecal excretion [179, 180]. An in vitro study showed the CSM had a higher affinity for OTA than bile salts and it was proposed that, in addition to effects on the enterohepatic circulation of OTA, alteration of the biliary bile salt pool may be a means in which CSM reduces OTA toxicity [181].…”
Section: Sequestering Agentsmentioning
confidence: 99%
“…Animal studies involving the use of CSM for OTA exposure have shown it accomplishes the therapeutic goal of reducing plasma levels of OTA while enhancing fecal excretion of the toxin bound to CSM. A study was able to demonstrate decreased nephrotoxicity in rats exposed to OTA that were given CSM, by reducing plasma and urine values of OTA while increasing fecal excretion [179, 180]. An in vitro study showed the CSM had a higher affinity for OTA than bile salts and it was proposed that, in addition to effects on the enterohepatic circulation of OTA, alteration of the biliary bile salt pool may be a means in which CSM reduces OTA toxicity [181].…”
Section: Sequestering Agentsmentioning
confidence: 99%